Identification of the main topics about cleaner production: A guide to directing sustainable industrial practices in the next decade - Santos, Vitor H. M. [UNESP]; Campos, Thalita L. R. [UNESP]; Espuny, Maximilian [UNESP]; Oliveira, Otávio J. [UNESP] (My University, 2021)
The increase in the consumption of goods and services around the world has intensified the negative environmental impacts of industrial companies. Consequently, the concern with these impacts appears more and more on the international agenda, intensifying the pressure for companies to use sustainable solutions. One of the most used solutions since ‘90s is the Cleaner Production (CP) strategy. However, the CP study has only highlighted in the past ten years. Thus, it is important that governments, companies, and universities become aware of the importance of improvements in this area. The objective of this work is to identify in the literature the level of development of the Cleaner Production strategy through the analysis of its state of the art. To this end, a bibliometric study of the articles published during the last five and a half years (2014-08.2019) on the studied topic in the Scopus and Web of Science databases was carried out. The results show the main authors, countries, journals, keywords, and areas of study related to the CP literature. The study presented in this research enables new research on CP practices, encouraging its development.
Keywords: Bibliometric Study; Cleaner Production; State of Art